Metal-Organic Framework-Based Engineered Materials—Fundamentals and Applications - Tahir Rasheed; Komal Rizwan; Muhammad Bilal; Hafiz M. N. Iqbal (Molecules, 2020)
Metal-organic frameworks (MOFs) are a fascinating class of porous crystalline materials constructed by organic ligands and inorganic connectors. Owing to their noteworthy catalytic chemistry, and matching or compatible coordination with numerous materials, MOFs offer potential applications in diverse fields such as catalysis, proton conduction, gas storage, drug delivery, sensing, separation and other related biotechnological and biomedical applications. Moreover, their designable structural topologies, high surface area, ultrahigh porosity, and tunable functionalities all make them excellent materials of interests for nanoscale applications. Herein, an effort has been to summarize the current advancement of MOF-based materials (i.e., pristine MOFs, MOF derivatives, or MOF composites) for electrocatalysis, photocatalysis, and biocatalysis. In the first part, we discussed the electrocatalytic behavior of various MOFs, such as oxidation and reduction candidates for different types of chemical reactions. The second section emphasizes on the photocatalytic performance of various MOFs as potential candidates for light-driven reactions, including photocatalytic degradation of various contaminants, CO2 reduction, and water splitting. Applications of MOFs-based porous materials in the biomedical sector, such as drug delivery, sensing and biosensing, antibacterial agents, and biomimetic systems for various biological species is discussed in the third part. Finally, the concluding points, challenges, and future prospects regarding MOFs or MOF-based materials for catalytic applications are also highlighted.